Media-Driven Promotion Strategies of Islamic Products: A Case Study of The Majlis Agama Islam Negeri Sembilan (MAINS) - Sofia Hayati Yusoff; Rosidayu Sabran; Rosninawati Hussin; Safiyyah Ahmad Sabri; Fauziah Hassan; Suria Hani A. Rahman; Nik Suhaida Nik Abdul Majid (Universiti Sains Islam Malaysia, 2025)
‘Abqari Journal, Volume 32 Issue 1 Page (1–10)